The longest journeys in Super Rugby: 11 years of travel and performance indicators - Lo, M.; Aughey, R. J.; Hopkins, W. G.; Gill, N.; Stewart, A. M. (Journal of Sports Sciences, 2019)
Regular air travel is common in sport. The aim of this study was to understand the extent to which travel has affected Super Rugby teams` performance from 2006, the first season with available Key Performance Indicators (KPIs), to 2016. Data were analysed with mixed linear models for the effects of number of time-zones crossed (east or west), travel duration, the away-match disadvantage, difference in ranking, a set of amendments to the laws of Rugby Union in 2008, a change in competition format (introduction of a conference system) in 2011, and a secular trend. In 2006, the predicted combined effects of travelling 24 h across 12 time-zones and playing away were trivial or small and negative but generally unclear for most of the KPIs in both directions of travel. In 2016 more effects were clear, small and negative for westward travel, while most effects for eastward travel were clear, small to moderate and negative. Most KPIs showed small to moderate increases over the 11 years, while difference in ranking, the introduction of new rules and game format led to mostly small changes. Changes in the physical demands of the game, and inadequate recovery time for long-haul travel can explain these effects.